2003
DOI: 10.1016/s0896-8411(02)00091-4
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 cytokines polarize thymocytes during T cell development in adult thymus organ cultures

Abstract: Peripheral T cells can be polarized towards type 1 or type 2 cytokine immune responses during TCR engagement. Because T cell selection by peptide plus self-MHC in the thymus requires TCR engagement, we hypothesized that type 1 cytokines may polarize developing T cells. We cultured thymi from BBDR rats in adult thymus organ cultures (ATOC) under type 1 cytokine conditions in the absence of exogenous antigen. Type 1 cytokine-conditioned ATOC generated cells that spontaneously secreted high levels of IFNgamma, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The adult thymic organ culture (ATOC) system has been used to study T cell development ex vivo (17). Co-culture of FoxP3-transduced iPS cells in ATOC for 2 weeks resulted in the generation of CD4 + CD25 + FoxP3 + Treg cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The adult thymic organ culture (ATOC) system has been used to study T cell development ex vivo (17). Co-culture of FoxP3-transduced iPS cells in ATOC for 2 weeks resulted in the generation of CD4 + CD25 + FoxP3 + Treg cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ing Thymus after Diet-Restriction Treatment Previous studies have reported decreased thymus weight relative to body weight after diet-restriction treatment. 3,18) Diet-restriction treatment for 48 h resulted in approximately 18% reduction in body weight (Fig. 1A).…”
Section: Expression Of Inflammatory Cytokines In the Involut-mentioning
confidence: 99%
“…It is also possible that thymocytes may be directed to cytokine synthesis by peripherally produced cytokines by inflammatory cells activated by PM exposure. It was evidenced that type 1 cytokines can polarize thymocyte differentiation in terms of surface markers expression and cytokine production in thymus organ cultures (207). Thus, the alterations in the thymocyte development may result from the changes in the thymic environment caused by complex xenobiotic exposure.…”
Section: Non‐receptor‐mediated Effectsmentioning
confidence: 99%